Investigation and characterization of ultrasonic reflection utilising spectrum unfolding for high value pure liquid materials - Abdul Hamid, Syamsul Bahrin; Alang Md Rashid, Nahrul Khair; Shafie, Amir Akramin; Toha, Siti Fauziah; Md Yusof, Hazlina; Sophian, Ali; Dandu, Mohd Akram (2020)
Edible oil is most often plant-based oils that have been extracted from various seeds. There are cases where the fully virgin edible oil was found to be a fraud. The adulterated edible oil indicates the intentional, fraudulent addition of extraneous, improper or cheaper ingredients puts into the oil or the dilution or removal of some valuable ingredient of the oil in order to increase profits. Hence, decrease the reliability of the Malaysian food product quality. This research was done by using two method – a) a time of flight obtained using the Texas Instrument board, TDC1000-TDC7200 EVM connected to an ultrasonic transducer with 1 MHz frequency and b) a Continuous Ultrasonic Wave (CUW) excitation using a through transmission technique, measuring using National Instruments Virtual Bench VB8012. The authors measured the time of flight and temperatures controlled from 20°C to 40°C of different vegetable oils. The value is observed and compared with other research from the literature review. From the study, time of flight values decreases exponentially while speed of sound value increases. From the study as well it was observed that ultrasonic technique could be utilized to identify different level of adulteration, with water being used as a calibration technique This research outcome is to investigate the quality value of the different type of edible oil while eliminates the issues where the quality of Malaysian food product is not reliable.